2017
DOI: 10.1016/j.pmedr.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Stress-related expectations about smoking cessation and future quit attempts and abstinence - a prospective study in daily smokers who wish to quit

Abstract: Smokers who wish to quit may refrain from doing so if they expect to experience more stress after haven given up. We test if stress-related expectations about smoking cessation are associated with quit attempts and abstinence among smokers who are motivated to quit. The study included 1809 daily smokers in Denmark in 2011–2013. Stress-related expectations (do you think you will be more, less or equally stressed as a non-smoker?) were measured at baseline. Quit attempts, 30-day point prevalence abstinence and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…Our results show that smoking cessation failure could impact the perceived stress of smokers. Skov-Ettrup et al reported that people who had previously attempted to quit smoking got more stressed when they had stopped smoking [33]. People who have relapsed from attempted smoking cessation might therefore need more effort to quit smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that smoking cessation failure could impact the perceived stress of smokers. Skov-Ettrup et al reported that people who had previously attempted to quit smoking got more stressed when they had stopped smoking [33]. People who have relapsed from attempted smoking cessation might therefore need more effort to quit smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Several barriers to smoking cessation have been identified. Stress 22 , 23 and urge to smoke or withdrawal symptoms were reported as barriers to quitting smoking among young adults. 24 Smokers undergoing the initial phase of quitting reported increased pain sensitivity and blunted stress responses compared with non-smokers, and their reported symptoms of withdrawal were associated with greater pain.…”
mentioning
confidence: 99%
“…Despite the results indicating that the number of quit attempts is positively associated with the intention to use and the attitude toward a cessation app, the definition of “quit attempt” in this study, though not uncommon [ 43 , 44 ], is chosen somewhat arbitrarily. First, the respondents were instructed to count a quit attempt when they did not smoke for over 24 hours.…”
Section: Discussionmentioning
confidence: 99%